Inverting the Conventional Site Selectivity of Cross-Coupling of 2,4-Dichloropyrimidines - Jackson, Oliver D.; Neufeldt, Sharon Rose (Synlett, 2025)
Cross-coupling and nucleophilic aromatic substitution reactions of 2,4-dihalopyrimidines generally favor reaction at the C4 site, especially in the absence of other substituents on the pyrimidine ring. Here, we review our recent discovery of reaction conditions that enable C2-selective Pd-catalyzed C–S coupling of unsubstituted 2,4-dichloropyrimidines, as well as some substituted derivatives. The unusual C2 selectivity complements previously established cross-coupling methods and raises interesting mechanistic questions about oxidative addition in cross-coupling catalytic cycles.
Keywords: Site selectivity; Protein kinase inhibitors; Cross-coupling; Thiopyrimidines; Catalysis; Nucleophilic aromatic substitution; Oxidative addition